2020
DOI: 10.1186/s12960-020-00521-8
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the clinical laboratory workforce in Cambodia: a case study of a mixed-method in-service training program to improve laboratory quality management system oversight

Abstract: Background Laboratory diagnostic testing service delivery and compliance with international standards for laboratory quality are directly influenced by laboratory workforce competency. Many hospital laboratories in constrained resource settings such as Cambodia struggle to cope with the training needs of laboratory professionals in an environment of competing healthcare development priorities. Resource-limited countries need an adaptable and effective approach to provide laboratory professional… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…A qualitative study of the remote mentoring program in Cambodia identified a number of recurring themes of benefits identified by participants, including that additional remote training reinforced concepts and provided peer learning opportunities and on-demand guidance; however, laboratories strongly preferred a more structured training format in the local language if online training was used. 19 The use of video conferencing technologies for medical education and consultation shows promise as a tool to create communities of practice between laboratorians and other health practitioners in the future, a practice that will prove all the more valuable during the COVID-19 pandemic, given that online platforms have become the primary means of accessing professional training and consultation for many medical professionals. [20][21][22] Notably, although attendance in formal, inperson training and the number of on-site visits were semi-controlled for variation and therefore could not be tested for a relationship to LQMS improvement, the relationship is expected.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study of the remote mentoring program in Cambodia identified a number of recurring themes of benefits identified by participants, including that additional remote training reinforced concepts and provided peer learning opportunities and on-demand guidance; however, laboratories strongly preferred a more structured training format in the local language if online training was used. 19 The use of video conferencing technologies for medical education and consultation shows promise as a tool to create communities of practice between laboratorians and other health practitioners in the future, a practice that will prove all the more valuable during the COVID-19 pandemic, given that online platforms have become the primary means of accessing professional training and consultation for many medical professionals. [20][21][22] Notably, although attendance in formal, inperson training and the number of on-site visits were semi-controlled for variation and therefore could not be tested for a relationship to LQMS improvement, the relationship is expected.…”
Section: Discussionmentioning
confidence: 99%
“…Due to advanced analytical technologies in medical laboratories, compared to the period of only 10 years ago [19,20], the job description and laboratory workload, the structure of the services they provide, and the role of medical biochemists has changed a lot in Serbia as well. Today, a biochemist is more involved in post-analytical phase, including verification of laboratory results and release of the laboratory test report and communication with a physician/clinical department (unexpected test results, need for new sampling, reflex testing per sample, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Need based training has been reported elsewhere to enhance Quality improvement when emphasize is put on actionable training needs. 15 The aim was to discuss challenges faced when executing GCLP and get an in-depth understanding on how to interpret and implement GCLP in their respective CRCs. The basic advanced model of training used has also been reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%